1996
DOI: 10.1111/1523-1747.ep12328177
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Vitro on the Role of αv and β1 Integrins in the Adhesion of Human Dermal Fibroblasts to Provisional Matrix Proteins Fibronectin, Vitronectin, and Fibrinogen

Abstract: Fibroblasts that migrate into a wound during the early stages of repair use cell surface integrins to interact with extracellular molecules as they move away from the interstitial matrix of normal tissue and into the provisional matrix of the wound. Therefore, to understand a critical phase of wound healing, it is necessary to understand the details of integrin involvement. Normal adult human dermal fibroblasts in culture express many receptors for the provisional matrix proteins fibronectin, vitronectin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 33 publications
3
66
0
Order By: Relevance
“…Gene therapy by Ad-mediated gene transfer requires that the target cells bind and take up the Ad vector efficiently (15,(20)(21)(22). In this study, we have demonstrated that CAR is rate limiting for infection by standard Ad5 vectors in primary α V integrin-positive cells and that the upregulation of CAR in such cells leads to increased binding of Ad, as well as more efficient expression of Ad transgene, both of which depend on a subgroup-specific fiber-CAR interaction.…”
Section: Discussionmentioning
confidence: 77%
“…Gene therapy by Ad-mediated gene transfer requires that the target cells bind and take up the Ad vector efficiently (15,(20)(21)(22). In this study, we have demonstrated that CAR is rate limiting for infection by standard Ad5 vectors in primary α V integrin-positive cells and that the upregulation of CAR in such cells leads to increased binding of Ad, as well as more efficient expression of Ad transgene, both of which depend on a subgroup-specific fiber-CAR interaction.…”
Section: Discussionmentioning
confidence: 77%
“…44 -46 It is possible that fibrin-mediated integrin ligation on the surface of fibroblasts causes a downstream intracellular signaling response via MAPK/ERK pathways that could potentially lead to an increase in collagen synthesis. 46,47 A similar process has been proposed to regulate the down-regulation of collagen synthesis by fibroblasts grown in collagen gels. 48 A persistence of fibrin due to reduced fibrinolysis may result in prolonged or enhanced cell-matrix interactions resulting in a further stimulation of procollagen gene expression.…”
Section: Discussionmentioning
confidence: 93%
“…The assay used in this study for measuring endothelial cell adhesion and spreading was modified from a previously described standard assay (21). Immulon 4 microtiter plates (Dynatech, Chantilly, VA) were coated with 50 l/well C1q (10 -50 g/ml) or other purified proteins diluted in 50 mM Tris (pH 7.4), 150 mM NaCl, and 0.1% NaN 3 .…”
Section: Endothelial Cell Adhesion and Spreading Assaymentioning
confidence: 99%